Corn production in Ollantaytambo during the 18th century - Glave, Luis Miguel (1980)
Corn is a cereal of humid and temperate climate. The warm valleys of the coast are its natural growth space. In the mountains, its cultivation is possible only in sheltered ravines, where the slope of the land makes it difficult to produce on a large scale. For its massive introduction into the Andes, it was necessary to fill in the slopes and channel the waters.